Retrograde tracing with recombinant rabies virus reveals correlations between projection targets and dendritic architecture in layer 5 of mouse barrel cortex - Larsen, DeLaine D.; Wickersham, Ian R.; Callaway, Edward M. (Frontiers in Neural Circuits, 2008)
A recombinant rabies virus was used as a retrograde tracer to allow complete fi lling of the axonal and dendritic arbors of identifi ed projection neurons in layer 5 of mouse primary somatosensory cortex (S1) in vivo. Previous studies have distinguished three types of layer 5 pyramids in S1: tall-tufted, tall-simple, and short. Layer 5 pyramidal neurons were retrogradely labeled from several known targets: contralateral S1, superior colliculus, and thalamus. The complete dendritic arbors of labeled cells were reconstructed to allow for unambiguous classifi cation of cell type. We confi rmed that the tall-tufted pyramids project to the superior colliculus and thalamus and that short layer 5 pyramidal neurons project to contralateral cortex, as previously described. We found that tall-simple pyramidal neurons contribute to corticocortical connections. Axonal reconstructions show that corticocortical projection neurons have a large superfi cial axonal arborization locally, while the subcortically projecting neurons limit axonal arbors to the deep layers. Furthermore, reconstructions of local axons suggest that tall-simple cell axons have extensive lateral spread while those of the short pyramids are more columnar. These differences were revealed by the ability to completely label dendritic and axonal arbors in vivo and have not been apparent in previous studies using labeling in brain slices.